Economic Trends in Africa : The Economic Performance of Sub-Saharan African Countries - Ballali, Daudi (IMF Working Papers; Working Paper, 1994)
This paper highlights selected recent developments in the economies of sub-Saharan Africa. It notes that the outlook for commodity prices has improved, and with it the outlook for economic activity beyond 1994; it also notes, however, the need for higher savings and investment to sustain growth over the medium term. The paper also covers two aspects of structural adjustment: the liberalization of exchange and trade systems, which has been extensive and has resulted in a sharp reduction in exchange market distortions; and the momentum of regional integration in the CFA countries and in the Southern Africa region.